PENGARUH CAR, NIM, LDR, NPL, BOPO,DAN KUALITAS AKTIVA PRODUKTIFTERHADAP PERUBAHAN LABA (Studi Empiris Pada Perusahaan Perbankan yang terdaftar di BEI) Tahun 2009–2011 - Nur Aini (Fakultas Ekonomika dan Bisnis, Universitas Stikubank, 2013)
This study aimed to examine the effect of the Capital Adequacy Ratio ( CAR ) , Net Interest Margin ( NIM ) , Loan to Deposit Ratio ( LDR ) , Non Performing Loan ( NPL ) , Operating Expenses and Operating Income ( ROA ) and Asset Quality ( KAP ) Changes to income , the banking companies listed in Indonesia Stock Exchange. The study took 61 banks listed on the Indonesia Stock Exchange in 2009-2011 as the sample. The independent variables in this study are the Capital Adequacy Ratio (CAR), Net Interest Margin (NIM) , Loan to Deposit Ratio (LDR) , Non Performing Loan (NPL) , Operating Expenses and Operating Income (OEOI/BOPO) and Asset Quality (AQ/KAP), and the dependent variable is Income Changes (IC/ROA). The Technique Applied in taking sample is purposive sampling .The data analysis applied is multiple linear regression based on OLS (Ordinary Least Squerst). Theresults of the study indicates that CAR variable has effect on the profit change with significance value at 0.011. NIMvariable has no effect on profit changes with significance value aat 0.306 , LDRvariablehas no significant effect on profit changes at 0.895, NPLvariable has positif effectbut, it is not significant on profit changes at 0.188, OEOI/BOPOBOPO variable has negatif effect but it is significant on profit changes at 0,044 and AQ/KAPvariable hassignificanteffect at 0,009.Key words: CAR, NIM, LDR, NPL, OEOI/BOPO, AQ/KAP and Profit change.